The use of the condom to prevent the transmission of HIV - Woodall, George J. (Medicina e Morale, 1998)
The aim of this article is to examine a question which has attracted attention from catholic moral theology, namely whether or not there are any circumstances in which the use of the condom may be legitimate as a protection against the spread of Human Immunodeficiency Virus (HIV). The issue is one of pressing pastoral concern as well as of theological interest, not least as far as it concerns spouses one of whom is HIV-positive. The scientific effectiveness of the condom as a barrier to the spread of the contagion has been addressed elsewhere. The approach here is a moral theological one. Various principles from the tradition of Catholic moral theology are examined (e.g. follow your conscience's legitimate defense, double effect, the lesser evil) to see whether a positive response to the question may be given. The second part of the study reviews these same principles and their application to the question. It is argued that spouses often will have a conditional contraceptive intention to prevent the birth of HIV-positive offspring, while more basically it is asked how an act which exposes the uncontaminated spouse to lethal contagion could be construed as an act of authentic love. More broadly, a careful examination of the criteria for advising the lesser evil queries whether a condom is a lesser evil given its unreliability, but also addresses the danger of scandal where a programmatic policy was to be in view. Particular mention is made of the danger of teachers giving such advice, in the light of their vocation and of their professional ethics. It is concluded that, however understandable it may appear at first sight to recommend the use of the condom to protect against HIV, from the objective standpoint it does not seem to be justifiable.